New records and distributional extensions of Peropteryx leucoptera, Gardnerycteris crenulatum, and Lampronycteris brachyotis in Bolivia - Poma-Urey, José L.; Acosta Salvatierra, Luis H.; Malpartida, Nicolas; Ramírez-Chaves, Héctor E.; Ochoa G., José (Therya Notes, 2023)
In the last 5 years, the knowledge of bats (Chiroptera) in Bolivia has advanced significantly, adding 10 species and an updated list for the country. Still, some species are represented by a few voucher specimens (n < 8), such as Peropteryx leucoptera (Emballonuridae), Gardnerycteris crenulatum, and Lampronycteris brachyotis (Phyllostomidae). Here, we provide new records that extend the geographic distribution of these species in Bolivia, along with morphometric data. Based on specimens collected and deposited in systematic collections, we performed qualitative and quantitative comparisons of external and craniodental variables with the original taxonomic descriptions of the 3 species. We also compiled and projected in maps the localities corresponding to historical records in Bolivia. The new records represent distributional extensions to 10 biogeographic provinces in Bolivia. The specimens of P. leucoptera come from the southeastern region of the country. For G. crenulatum and L. brachyotis we present the southernmost and the easternmost records in Bolivia, respectively. The specimens of P. leucoptera tend to be smaller than others collected in the region, while the specimens of G. crenulatum are slightly larger than those reported from other countries. The new records extend the known geographic ranges of these species between 197 and 736 km in Bolivia. We recommend increasing efforts to update the geographic distributions of other species with scarce records in Bolivia.